2007
DOI: 10.1021/jp072258i
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Response in Crystalline Iβ Cellulose:  A Molecular Dynamics Study

Abstract: The influence of temperature on structure and properties of the cellulose Ibeta crystal was studied by molecular dynamics simulations with the GROMOS 45a4 force-field. At 300 K, the modeled crystal agreed reasonably with several sets of experimental data, including crystal density, corresponding packing and crystal unit cell dimensions, chain conformation parameters, hydrogen bonds, Young's modulus, and thermal expansion coefficient at room temperature. At high-temperature (500 K), the cellulose chains remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
134
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(164 citation statements)
references
References 59 publications
29
134
1
Order By: Relevance
“…Chain tilt occurred from the beginning of our simulations, consistent with observations in other MD simulations of cellulose using different force fields, crystalline models, and finite models (Bergenstråhle et al, 2007;Matthews et al, 2011aMatthews et al, , 2012Zhang et al, 2011;Chen et al, 2014). When microfibrils were viewed from the nonreducing end, origin layers had a clockwise tilt (positive) compared with the crystal structure, while the center layers had an anticlockwise tilt (negative; Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Chain tilt occurred from the beginning of our simulations, consistent with observations in other MD simulations of cellulose using different force fields, crystalline models, and finite models (Bergenstråhle et al, 2007;Matthews et al, 2011aMatthews et al, , 2012Zhang et al, 2011;Chen et al, 2014). When microfibrils were viewed from the nonreducing end, origin layers had a clockwise tilt (positive) compared with the crystal structure, while the center layers had an anticlockwise tilt (negative; Fig.…”
Section: Resultssupporting
confidence: 90%
“…A 36-chain, hexagonal-shaped model was suggested by Ding and Himmel (2006) and thought to be an optimal model from transmission electron microscopy and atomic force microscopy studies (Ding et al, 2014), because the cellulose synthase rosette complex from which cellulose is produced in plants is thought to be composed of 36 cellulose synthase catalytic proteins (Herth, 1983). Other 36-chain complexes have been suggested that have a square shape, in which the hydrophobic (100) and hydrophilic (010) faces are exposed to solvent (Mazeau, 2005;Matthews et al, 2006;Bergenstråhle et al, 2007), and a diamond-like shape where two hydrophilic (110 and 1-10) faces are exposed (Matthews et al, 2006;Zhang et al, 2011;Chen et al, 2014). However, there is now evidence from Rotation about the O5-C5-C6-O6 dihedral allows for three different conformations of the C6 exocyclic group of each Glc monomer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, numerous studies use MD simulations to study the influence of temperature on, e.g., structure and properties of cellulose , 16,17,18 and shorter oligosaccharides, 19,20,21 the interactions between carbohydrates and other molecular species, 22,23,24 and, not the least, dissolution of cellulose in, e.g., ionic liquids, 25,26 and water. 27 Recently, Shen et al 28 published an extensive simulation study with the GLYCAM04 parameter set (available for download at www.glycam.org) in which the conformational flexibility of shortchain cellooligomers was investigated as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Significant observations include an "untwisting" due to the formation of a three-dimensional hydrogen bonding network near the center chains of the 36-chain model (DP 40), for which the authors suggest arise from conformational changes of the hydroxymethyl groups. Bergenstråhle et al also studied the influence of temperature on the properties of the cellulose Iβ crystal using molecular dynamics simulation with the GROMOS 45a4 force field and found that at room temperature, the crystal structure could be sufficiently reproduced in terms of crystal density, unit cell dimensions and packing, whereas above 450 K, changes in the orientation of the hydroxymethyl group caused a shift in hydrogen bonding patterns and unit cell dimensions (Bergenstråhle et al, 2007).…”
Section: Structure Of Cellulosementioning
confidence: 99%